Influence of Strength Level on Performance Enhancement Using Resistance Priming. Issue 1 (January 2022) - Nishioka, Takuya; Okada, Junichi
Abstract : Abstract: Nishioka, T and Okada, J. Influence of strength level on performance enhancement using resistance priming. J Strength Cond Res 36(1): 37–46, 2022—The current study aimed to investigate (a) whether resistance priming was effective in enhancing jump performance for both stronger and weaker individuals and (b) how resistance priming influences the lower-body force-velocity profile. A total of 20 resistance-trained men performed priming and control conditions 72–144 hours apart in a randomized and counterbalanced order. Jump performances (0 and 40% 1 repetition maximum [1RM] squat jump, 0 and 40% 1RM countermovement jump [CMJ] and drop jump) were assessed before and 24 hours after the priming session, and before and 24 hours after rest (control). Priming session-induced percentage change in 0% 1RM CMJ height was positively correlated with the individual's relative half squat 1RM ( r = 0.612, p ⩽ 0.05). Using the median split method, subjects were divided into stronger (relative half squat 1RM = 1.93–2.67 kg·kg −1 ) and weaker (relative half squat 1RM = 1.37–1.92 kg·kg −1 ) groups and subsequently analyzed. The stronger group showed specific improvement in 0% 1RM CMJ performance 24 hours after the priming session ( p ⩽ 0.05), whereas the weaker group showed no improvement in any of their jump performances. Moreover, the priming session enhanced the theoretical maximum velocity ( p ⩽ 0.05), but not the theoretical maximum force during CMJ in the stronger group; whereas none of the force-velocity profile variables were enhanced in the weaker group. These results suggest that stronger individuals are more likely to experience performance enhancement using resistance priming, which may be movement- and velocity-specific. Abstract : Supplemental Digital Content is Available in the Text.